Energieoptimale Fahrdynamikregelung mehrmotoriger Elektrofahrzeuge - Eckert, Michael (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2014)
Within the scope of this work a generic approach to the control of multiple-drive electric vehicles is evolved. An analysis of the overall system with respect to the exploitable degrees of freedom for wheel torque control reveals that several possible solutions for distributing wheel torque exist in certain driving situations. This characteristic of over-actuated systems is exploited in order to pursue further subordinate objectives from from a control perspective.